REVITALISASI KOMUNIKASI ANALOG DI KOMUNITAS KELUARGA MUDA INDONESIA - Nurul Ifadhah; Irwansyah Irwansyah (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Handwritting into book is the most ancient form of analog communication and a means of remote communication that was first present in human life. However, just like any other communication product, writing on books (journaling) slowly begins to be eroded by technology dermination. The culture of analog writing shifts to typing. The decline in interest analog writing is seen from the results of research and regulations in some countries that no longer require the younger generation to have certain skills of writing. In fact, analog writing activities are scientifically proven to be mentally healthy. The situation in Indonesia is slightly different from the presence of the government that requires handwritten classes for elementary children, and the growing writing market in young family communities. Journaling in the millenial mother community is a process to get a more conscious lifestyle. This research aims to understand the revitalization process of an analog communication to remain favored by people who have become accustomed to consuming communication information technology. Through the Case Study it was found that journaling as analog communication is able to maintain its existence because of the revitalization of ideas through interdisciplinary and multidisciplinary collaboration in the scope of communication science.